Employee engagement at Pejabat Daerah Baling: a case study / Nur Diana Akma Hashim and Zatun Najahah Muhammad Husin - Hashim, Nur Diana Akma; Muhammad Husin, Zatun Najahah (2012)
Nowadays, employee engagement seems to be the controversial topic in the management world. Therefore, employees need to be on the path in order to get all of members in organization are engaged to the work. This study was held for the purpose of identified the factors that lead to employee's engagement in the workplace and the relationship between those variables. The claim was made that engagement is needed for higher levels of firm performance, and consultant studies estimate that only 14 percent to 30 percent of employees are engaged at work (Welbourne, 2007). It is crucial to analyze the factors that lead to the level of employee engagement at work and steps to be taken as to attract the employees' attention and interest towards the organization. There are several problems that occurred in the workplace that the researchers have chosen to be in the research area. The problems consist of leadership style, the workplace culture, behavioural engagement and the distribution of resources. The company needs to take corrective actions to overcome the problems among the employees. Role of the leaders are important in determining the engagement of employees. The job involvement and fairly distribution of resources among employees will attract the employees to get engaged with their job.